Neutrophil subpopulations and their activation potential in patients with antiphospholipid syndrome and healthy individuals. (7th October 2020) - Mauracher, Lisa-Marie; Krall, Moritz; Roiß, Johanna; Hell, Lena; Koder, Silvia; Hofbauer, Thomas M; Gebhart, Johanna; Hayden, Hubert; Brostjan, Christine; Ay, Cihan; Pabinger, Ingrid
Abstract: Objectives: Patients with APS are at increased risk of thromboembolism. Neutrophils have been shown to play a role in inducing thrombosis. We aimed to investigate differences in neutrophil subpopulations, their potential of activation and neutrophil extracellular trap (NET) formation comparing high and low-density neutrophils (HDNs/LDNs) as well as subpopulations in patients with APS and controls to gain deeper insight into their potential role in thrombotic manifestations in patients with APS. Methods: HDNs and LDNs of 20 patients with APS and 20 healthy donors were isolated by density gradient centrifugation and stimulated. Neutrophil subpopulations, their activation and NET release were assessed by flow cytometry. Results: LDNs of both groups showed higher baseline activation, lower response to stimulation (regulation of activation markers CD11b/CD66b), but higher NET formation compared with HDNs. In patients with APS, the absolute number of LDNs was higher compared with controls. HDNs of APS patients showed higher spontaneous activation [%CD11b high: median (interquartile range): 2.78% (0.58–10.24) vs 0.56% (0.19–1.37)] and response to stimulation with ionomycin compared with HDNs of healthy donors [%CD11b high: 98.20 (61.08–99.13) vs 35.50% (13.50–93.85)], whereas no difference was found in LDNs. NET formation was increased in patients' HDNs upon stimulation. Conclusion: HDNs and LDNs act differently, unstimulated and upon various stimulations in both healthy controls and APS patients. Differences in HDNs and LDNs between patients with APS and healthy controls indicate that neutrophils may enhance the risk of thrombosis in these patients and could thus be a target for prevention of thrombosis in APS.